Recent Developments in the Electrochemical Determination of Sulfonamides - Fu, Li; Zhang, Xinyi; Ding, Su; Chen, Fei; Lv, Yanfei; Zhang, Huaiwei; Zhao, Shichao (Current Pharmaceutical Analysis, 2022)
Background: Sulfonamides are the anti-bacterial and anti-inflammatory drugs synthesized, which are widely used as medical and veterinary antibiotics. However, the excess dosage of sulfonamides can harm human health. Drug residues in animal products also can harm human health through the food chain. The long-term consumption of animal food containing drug residues will cause some toxicity and side effects on human body functions, which will seriously threaten human health. Methods: Electroanalytical methods are attracting much attention because of their advantage over conventional methods, as they are quick, low-cost, high sensitivity, and portable. This review examines the progress made in the selective electrochemical determination of sulfonamides in the last 20 years. Results: In this review, we describe the development of electrochemical methods for sulfonamides determination. Then, we pay special attention to the detection of sulfonamides using molecular imprinting technology. The linear detection range with the limit of detection has been listed for comparison. Conclusion: Electrochemical determination of sulfonamides is a fast, simple, sensitive, and cost-effective approach. The surface modification of commercial electrodes can significantly improve the sensing performance.
Keywords: Electrochemical sensors